Repercussão da ingestão crônica de dieta termolizada em parâmetros morfo-funcionais do tecido hepático - Silva, Elisa Batista Oliveira e (2012)
AGEs, Advanced Glycation End Products, are heterogeneous compounds with pro-oxidant and pro-inflammatory properties. These compounds are formed in the body (particularly under conditions of hyperglycemia and oxidative stress) and in environment, being the diet their main source exogenous. Neutral or alkaline food, subjected heat-treated at temperatures above 100°C with low humidity, for prolonged periods had increased formation of AGEs, conditions frequently encountered in the typical Western diet, which is a source of high levels of AGEs. The heat treatment of food, in addition to form AGEs, contributes to reducing labile vitamin with anti-glycation action and essential for humans, thiamin. The chronic consumption of diet rich in AGEs and deficient in thiamin are conditions that promote oxidative stress, carbonyl stress and persisted inflammation, contributing to the aging process with the development of several chronic diseases. When absorbed, dietary AGEs are added to those produced in the body increasing your body pool, through the kidney and liver, undergo catabolism and degradation to be eliminated. In particular, the liver is the main organ of clearance and catabolism of AGEs, becoming an easy target for the damaging effects of AGEs. In cases of thiamin deficiency, the hepatocyte is more susceptible to glyoxal, a carbonyl highly reactive precursor of AGEs, and AGEs themselves, with consequent loss of glyoxal metabolism in the liver. Supplementation of thiamin results in cytoprotection, restoration of the glyoxal detoxification, reduction of lipid peroxidation and the formation of reactive oxygen species. These elements led to the investigation of the effects of chronic consumption of thermolyzed diet, experimental model of high intake of AGEs, associated with different levels of thiamin in morpho-functional aspects of liver tissue in adult rats. For this purpose, male Wistar rats, five months old, were divided into four experimental groups according to the offered diets: standard commercial diet, control (C); thermolyzed (T), standard diet autoclaved at 121.5°C for 30 min; thermolyzed with level 1 thiamin (TT1), thiamin 6 mg/kg of diet; and thermolyzed with level 2 thiamin (TT2), 120 mg thiamin/kg of diet. After 23 weeks of treatment, animals were anesthetized and proceeded to collect samples of liver and blood, to histological analysis of hepatic tissue and tests serum biochemical of hepatic function and injury. The chronic consumption of thermolyzed diet did not promote the appearance of morphological and functional alterations in adult rat blood and liver. It is possible to consider the composition of base diet used in the experiment may have contributed to the results obtained. This study draws attention to the importance of studies to clarify the involvement of different components food for the formation of AGEs in food, which contribute to the establishment of recommendations for promoting a healthy diet, contributing to the prevention chronic diseases, including those affecting the hepatic tissue.